Contains fusin co-polymer

By adjusting the content and melting flow rate of hexafluoropropylene and perfluoroether ethylene units, a fluorocarbon copolymer with excellent performance was prepared, which solved the problem of insufficient performance of fluorocarbon polymers in the prior art and achieved the improvement of multiple properties.

JP7660534B2Active Publication Date: 2025-04-11DAIKIN INDUSTRIES LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2022029720
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-02-26
Filing Date
2022-02-28
Publication Date
2025-04-11
Estimated Expiration
2042-02-28

AI Technical Summary

Technical Problem

The prior art is difficult to provide a fluorocarbon polymer with excellent wear resistance, oxidation resistance, thermal aging resistance, water vapor permeability, low oxygen permeability, high temperature rigidity, stretch creep resistance and injection pressure resistance.

Method used

A fluorocarbon copolymer with excellent properties was prepared by adjusting the content, melting rate and number of functional groups of hexafluoropropylene units and perfluoroether ethylene units.

Benefits of technology

It has achieved significant improvements in fluorocarbon copolymers in wear, oxidation, thermal aging, water vapor permeability, low oxygen permeability, high temperature rigidity, stretch creep resistance and injection pressure resistance, and is suitable for a variety of high-performance applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007660534000001
    Figure 0007660534000001
  • Figure 0007660534000002
    Figure 0007660534000002
  • Figure 0007660534000003
    Figure 0007660534000003
Patent Text Reader

Abstract

To provide a fluorine-containing copolymer which is excellent in wear resistance at 140°C, ozone resistance, thermal aging resistance, low water vapor permeability, low oxygen permeability, rigidity at a high temperature of 100°C, tensile creep resistance properties at 110°C and extrusion moldability.SOLUTION: There is provided a fluorine-containing copolymer containing a tetrafluoroethylene unit, a hexafluoropropylene unit and a perfluoro (ethyl vinyl ether) unit, wherein the content of the hexafluoropropylene unit is 10.5 to 11.6 mass% based on the total monomer units, the content of the perfluoro (ethyl vinyl ether) unit is 1.2 to 2.4 mass% based on the total monomer units, the melt flow rate at 372°C is 28.0 to 40.0 g / 10 min and the total number of -CF2H, a carbonyl group-containing terminal group, -CF=CF2 and -CH2OH is 25 or less per main-chain carbon number of 106.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a fluorine-containing copolymer. [Background technology]

[0002] Patent Document 1 describes a non-staining article for contact with non-food liquids and foods, in which at least the surface of the article that comes into contact with the non-food liquids or foods is a melt-processable perfluoropolymer that remains polymerized and is free of ionic species, dispersants, and halocarbon solvent polymerization medium.

[0003] Patent Document 2 describes a culture vessel at least a part of which is made of a fluorine-containing molten resin. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Special Publication No. 2009-540105 [Patent Document 2] Special Publication No. 6-40813 Summary of the Invention [Problem to be solved by the invention]

[0005] An object of the present disclosure is to provide a fluorocopolymer which is excellent in abrasion resistance at 140°C, ozone resistance, heat aging resistance, water vapor permeability, low oxygen permeability, rigidity at a high temperature of 100°C, tensile creep resistance at 110°C, and extrusion moldability. [Means for solving the problem]

[0006] According to the present disclosure, there is provided a fluorine-containing copolymer containing tetrafluoroethylene units, hexafluoropropylene units and perfluoro(ethyl vinyl ether) units, the content of the hexafluoropropylene units being 10.5 to 11.6 mass% based on the total monomer units, the content of the perfluoro(ethyl vinyl ether) units being 1.2 to 2.4 mass% based on the total monomer units, the melt flow rate at 372°C being 28.0 to 40.0 g / 10 min, and -CF 2 H, carbonyl-containing end group, -CF=CF 2 and -CH 2 The total number of OH is 10 6 The present invention provides a fluorine-containing copolymer having 25 or less units per unit.

[0007] The content of the hexafluoropropylene unit is preferably 10.7 to 11.5% by mass based on the total monomer units. The content of perfluoro(ethyl vinyl ether) units is preferably 1.4 to 1.8% by mass based on the total monomer units. The melt flow rate at 372° C. is preferably 30.0 to 39.9 g / 10 min. The melt flow rate at 372° C. is preferably 33.0 to 39.9 g / 10 min.

[0008] The present disclosure also provides an injection-molded article containing the above-mentioned fluorocopolymer.

[0009] The present disclosure also provides a covered electric wire having a covering layer containing the above-mentioned fluorine-containing copolymer.

[0010] The present disclosure also provides a molded article containing the above-mentioned fluorocopolymer, which is a container, a tube, a film or a wire coating. Effect of the Invention

[0011] According to the present disclosure, it is possible to provide a fluorocopolymer which is excellent in abrasion resistance at 140°C, ozone resistance, heat aging resistance, water vapor permeability, low oxygen permeability, rigidity at a high temperature of 100°C, tensile creep resistance at 110°C, and extrusion moldability. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] Specific embodiments of the present disclosure will be described in detail below, but the present disclosure is not limited to the following embodiments.

[0013] The fluorine-containing copolymer of the present disclosure contains tetrafluoroethylene (TFE) units, hexafluoropropylene (HFP) units and perfluoro(ethyl vinyl ether) (PEVE) units.

[0014] Patent Document 2 describes that incubators are required to satisfy various properties, such as light transmittance, low moisture permeability, durability, and chemical resistance, in order to provide an environment for culturing cells, tissues, organs, etc. of animals and plants, or microorganisms. Patent Document 2 also proposes an incubator that is at least partially made of a fluorine-containing molten resin as an unbreakable incubator that is not invaded by germs, has good breathability and low moisture permeability, and has light transmittance comparable to that of glass. Such an incubator is suitable for culturing some bacteria and microorganisms, but cannot be used suitably for culturing anaerobic bacteria or bacteria that need to be cultured while adjusting the humidity inside the incubator.

[0015] Therefore, we have intensively studied materials for containers that can be used for anaerobic bacteria, and have found that a fluorocopolymer containing TFE units, HFP units and PEVE units can be used, and that by appropriately adjusting the contents of HFP units and PEVE units, the melt flow rate and the number of functional groups of the fluorocopolymer, a fluorocopolymer that can give a molded article that is easy to permeate water vapor and difficult to permeate oxygen can be obtained. Furthermore, the molded article obtained from such a fluorocopolymer is excellent in 140°C abrasion resistance, ozone resistance, heat aging resistance, rigidity at high temperature of 100°C and tensile creep resistance at 110°C, so that a container that can withstand sterilization at high temperatures and sterilization using ozone water or hydrogen peroxide water and is difficult to wear even when used repeatedly can be obtained.

[0016] Moreover, such a fluorocopolymer can be easily molded at a low extrusion pressure, and therefore, a molded article such as a film can be easily obtained by molding the fluorocopolymer of the present disclosure by injection molding or extrusion molding.

[0017] The fluorocopolymers of the present disclosure are melt-processable fluororesins, which means that the polymer can be melted and processed using conventional processing equipment such as extruders and injection molding machines.

[0018] The content of HFP units in the fluorocopolymer is 10.5 to 11.6% by mass, preferably 10.6% by mass or more, more preferably 10.7% by mass or more, and preferably 11.5% by mass or less, based on the total monomer units. If the content of HFP units is too low, a molded product having excellent 140°C abrasion resistance and water vapor permeability cannot be obtained. If the content of HFP units is too high, a molded product having excellent 100°C high-temperature rigidity and 110°C tensile creep resistance cannot be obtained.

[0019] The content of the PEVE unit in the fluorocopolymer is 1.2 to 2.4% by mass, preferably 1.3% by mass or more, more preferably 1.4% by mass or more, preferably 2.3% by mass or less, more preferably 2.2% by mass or less, even more preferably 2.1% by mass or less, still more preferably 2.0% by mass or less, particularly preferably 1.9% by mass or less, and most preferably 1.8% by mass or less. By having the content of the PEVE unit within the above range, a molded product having excellent 140°C abrasion resistance, ozone resistance, heat aging resistance, water vapor permeability, low oxygen permeability, rigidity at high temperature at 100°C, tensile creep resistance at 110°C, and extrusion moldability can be obtained. If the content of the PEVE unit is too low, a molded product having excellent 140°C abrasion resistance, ozone resistance, and heat aging resistance cannot be obtained.

[0020] The content of TFE units in the fluorine-containing copolymer is preferably 86.0% by mass or more, more preferably 86.3% by mass or more, even more preferably 86.5% by mass or more, still more preferably 86.7% by mass or more, preferably 88.3% by mass or less, more preferably 88.1% by mass or less, and even more preferably 87.9% by mass or less, based on the total monomer units. The content of TFE units may be selected so that the total content of HFP units, PEVE units, TFE units and other monomer units is 100% by mass.

[0021] As long as the fluorinated copolymer of the present disclosure contains the above three monomer units, it may be a copolymer containing only the above three monomer units, or a copolymer containing the above three monomer units and other monomer units.

[0022] The other monomer is not particularly limited as long as it is a monomer copolymerizable with TFE, HFP and PEVE, and may be a fluoromonomer or a non-fluorine-containing monomer.

[0023] Fluoromonomers include chlorotrifluoroethylene, vinyl fluoride, vinylidene fluoride, trifluoroethylene, hexafluoroisobutylene, CH 2 =CZ 1 (CF 2 ) n Z 2 (In the formula, Z 1 is H, F, or Z 2 is H, F or Cl, and n is an integer from 1 to 10), 2 =CF-ORf 1 (In the formula, Rf 1 Perfluoro(alkyl vinyl ether) [PAVE] (excluding PEVE) represented by perfluoroalkyl group having 1 to 8 carbon atoms, CF 2 =CF-O-CH 2 -Rf 2 (In the formula, Rf 2 is preferably at least one selected from the group consisting of alkyl perfluorovinyl ether derivatives represented by a perfluoroalkyl group having 1 to 5 carbon atoms, perfluoro-2,2-dimethyl-1,3-dioxole [PDD], and perfluoro-2-methylene-4-methyl-1,3-dioxolane [PMD].

[0024] CH 2 =CZ 1 (CF 2 ) n Z 2 As a monomer represented by CH 2 =CFCF 3 , C.H. 2 =CH-C 4 F 9 , C.H. 2 =CH-C 6 F 13 , C.H. 2 =CF-C 3 F 6 Examples include H.

[0025] CF 2 =CF-ORf 1 As the perfluoro(alkyl vinyl ether) represented by the formula: CF 2 =CF-OCF 3, C.F. 2 =CF-OCF 2 CF 2 CF 3 etc.

[0026] Examples of the fluorine-free monomer include hydrocarbon monomers copolymerizable with TFE, HFP, and PEVE. Examples of the hydrocarbon monomer include alkenes such as ethylene, propylene, butylene, and isobutylene; alkyl vinyl ethers such as ethyl vinyl ether, propyl vinyl ether, butyl vinyl ether, isobutyl vinyl ether, and cyclohexyl vinyl ether; vinyl acetate, vinyl propionate, vinyl n-butyrate, vinyl isobutyrate, vinyl valerate, vinyl pivalate, vinyl caproate, vinyl caprylate, vinyl caprate, vinyl versatate, vinyl laurate, vinyl myristate, vinyl palmitate, vinyl stearate, vinyl benzoate, vinyl para-t-butylbenzoate, vinyl cyclohexanecarboxylate, vinyl monochloroacetate, vinyl adipate, and the like. vinyl esters such as vinyl allyl ether, vinyl acrylate, vinyl methacrylate, vinyl crotonate, vinyl sorbate, vinyl cinnamate, vinyl undecylenate, vinyl hydroxyacetate, vinyl hydroxypropionate, vinyl hydroxybutyrate, vinyl hydroxyvalerate, vinyl hydroxyisobutyrate, and vinyl hydroxycyclohexanecarboxylate; alkyl allyl ethers such as ethyl allyl ether, propyl allyl ether, butyl allyl ether, isobutyl allyl ether, and cyclohexyl allyl ether; and alkyl allyl esters such as ethyl allyl ester, propyl allyl ester, butyl allyl ester, isobutyl allyl ester, and cyclohexyl allyl ester.

[0027] The fluorine-free monomer may also be a functional group-containing hydrocarbon monomer that can be copolymerized with TFE, HFP and PEVE.The functional group-containing hydrocarbon monomer may, for example, be hydroxyalkyl vinyl ethers such as hydroxyethyl vinyl ether, hydroxypropyl vinyl ether, hydroxybutyl vinyl ether, hydroxyisobutyl vinyl ether, hydroxycyclohexyl vinyl ether, etc.; fluorine-free monomers having glycidyl groups such as glycidyl vinyl ether and glycidyl allyl ether, fluorine-free monomers having amino groups such as aminoalkyl vinyl ether and aminoalkyl allyl ether, fluorine-free monomers having amide groups such as (meth)acrylamide and methylol acrylamide, bromine-containing olefins, iodine-containing olefins, bromine-containing vinyl ethers, iodine-containing vinyl ethers, fluorine-free monomers having nitrile groups, etc.

[0028] The content of other monomer units in the fluorine-containing copolymer of the present disclosure is preferably 0 to 2.3 mass%, more preferably 1.1 mass% or less, further preferably 0.5 mass% or less, and particularly preferably 0.1 mass% or less, based on the total monomer units.

[0029] The melt flow rate (MFR) of the fluorine-containing copolymer is 28.0 to 40.0 g / 10 min, preferably 28.1 g / 10 min or more, more preferably 29.0 g / 10 min or more, even more preferably 30.0 g / 10 min or more, particularly preferably 32.0 g / 10 min or more, most preferably 33.0 g / 10 min or more, and preferably 39.9 g / 10 min or less. If the MFR is too low, a molded product excellent in low oxygen permeability, rigidity at a high temperature of 100°C, and extrusion moldability cannot be obtained. If the MFR is too high, a molded product excellent in ozone resistance and heat aging resistance cannot be obtained.

[0030] In the present disclosure, the melt flow rate is a value obtained in accordance with ASTM D-1238 using a Melt Indexer G-01 (manufactured by Toyo Seiki Seisakusho) at 372°C under a load of 5 kg, and expressed as the mass of polymer flowing out per 10 minutes (g / 10 minutes) from a die having an inner diameter of 2 mm and a length of 8 mm.

[0031] The MFR can be adjusted by adjusting the type and amount of a polymerization initiator used when polymerizing the monomers, the type and amount of a chain transfer agent, and the like.

[0032] Fluorine-containing copolymer main chain carbon number 10 6 -CF per piece 2 H, carbonyl-containing end group, -CF=CF 2 and -CH 2 The total number of OH groups is not more than 25. The total number of these functional groups is preferably less than 21. When the total number of these functional groups is within the above range, a molded product can be obtained that has excellent ozone resistance and is less likely to elute fluorine ions in chemical solutions such as hydrogen peroxide.

[0033] Examples of the carbonyl-containing end group include -COF, -COOH, -COOR (where R is an alkyl group), -CONH 2 and -O(C=O)OR (R is an alkyl group). The type of alkyl group (R) in -COOR and -O(C=O)OR is determined by the polymerization initiator, chain transfer agent, etc. used in producing the fluorine-containing copolymer. For example, -CH 3 and the like are alkyl groups having 1 to 6 carbon atoms.

[0034] The type of functional group and the number of functional groups can be identified by infrared spectroscopy.

[0035] Specifically, the number of functional groups is measured by the following method. First, the above-mentioned fluorocopolymer is molded by cold pressing to prepare a film having a thickness of 0.25 to 0.30 mm. This film is analyzed by Fourier transform infrared spectroscopy to obtain an infrared absorption spectrum of the above-mentioned fluorocopolymer, and a difference spectrum with a base spectrum in which the copolymer is completely fluorinated and no functional groups are present is obtained. From the absorption peaks of specific functional groups appearing in this difference spectrum, the number of carbon atoms in the above-mentioned fluorocopolymer is determined according to the following formula (A): 6 Calculate the number of functional groups per unit, N.

[0036] N=I×K / t (A) I: Absorbance K: Correction coefficient t: film thickness (mm)

[0037] For reference, the absorption frequencies, molar absorption coefficients, and correction coefficients for several functional groups are shown in Table 1. The molar absorption coefficients were determined from the FT-IR measurement data of low-molecular-weight model compounds. [Table 1]

[0038] -CH 2 CF 2 H, -CH 2 COF, -CH 2 COOH, -CH 2 COOCH 3 , -CH 2 CONH 2 The absorption frequencies of -CF 2 H, -COF, -COOH free and -COOH bonded, -COOCH 3 , -CONH 2 Absorption frequency of tens of Kaiser (cm -1 ) lower.

[0039] For example, the functional group of -COF is -CF 2 Absorption frequency due to COF: 1883 cm -1The number of functional groups determined from the absorption peak of -CH 2 Absorption frequency due to COF: 1840cm -1 The number of functional groups is the sum of the number of functional groups determined from the absorption peaks of

[0040] Also, -CF 2 The number of H groups was measured using a nuclear magnetic resonance apparatus at a temperature of (polymer melting point + 20)°C. 19 F-NMR measurement was performed using -CF 2 It can also be calculated from the peak integral value of H group.

[0041] -CF 2 The functional groups such as H groups are functional groups present at the main chain end or side chain end of the fluorine-containing copolymer, and functional groups present in the main chain or side chain. These functional groups are introduced into the fluorine-containing copolymer by, for example, a chain transfer agent or a polymerization initiator used in producing the fluorine-containing copolymer. For example, alcohol is used as a chain transfer agent, or -CH 2 When a peroxide having an OH structure is used, -CH 2 In addition, by polymerizing a monomer having a functional group, the functional group is introduced into the side chain terminal of the fluorine-containing copolymer.

[0042] A fluorocopolymer having the number of functional groups within the above range can be obtained by subjecting a fluorocopolymer having such functional groups to a wet heat treatment, a fluorination treatment, or the like. The fluorocopolymer of the present disclosure is preferably one that has been subjected to a wet heat treatment or a fluorination treatment, and more preferably one that has been subjected to a fluorination treatment. The fluorocopolymer of the present disclosure is preferably one that has been subjected to a wet heat treatment or a fluorination treatment. 3 It is also preferred that the compound has a terminal group.

[0043] The melting point of the fluorine-containing copolymer is preferably 220 to 290° C., more preferably 240 to 280° C. When the melting point is within the above range, it is possible to obtain a molded product which is more excellent in 140° C. abrasion resistance, ozone resistance, heat aging resistance, water vapor permeability, low oxygen permeability, rigidity at a high temperature of 100° C., 110° C. tensile creep resistance and extrusion moldability.

[0044] In this disclosure, melting points can be measured using a differential scanning calorimeter (DSC).

[0045] The oxygen permeability coefficient of the fluorocopolymer is preferably 710 cm 3 mm / (m 2 The fluorocopolymer of the present disclosure has an excellent low oxygen permeability because the contents of HFP units and PEVE units, the melt flow rate (MFR) and the number of functional groups are appropriately adjusted.

[0046] In the present disclosure, the oxygen permeability coefficient can be measured under the conditions of a test temperature of 70° C. and a test humidity of 0% RH. The oxygen permeability coefficient can be specifically measured by the method described in the Examples.

[0047] The fluorocopolymer of the present disclosure preferably has a water vapor permeability of 17.0 g cm / m 2 By having the water vapor permeability within the above range, when a container such as a culture vessel is produced using the fluorocopolymer of the present disclosure, the humidity inside the container can be appropriately controlled.

[0048] The amount of eluted fluorine ions of the fluorocopolymer of the present disclosure detected in an immersion test in hydrogen peroxide solution is preferably 4.0 ppm or less, more preferably 3.0 ppm or less, more preferably 2.8 ppm or less, by mass. When the amount of eluted fluorine ions is within the above range, when a container such as a culture vessel is produced using the fluorocopolymer of the present disclosure, the influence of the eluted fluorine ions is almost eliminated.

[0049] In the present disclosure, the immersion test in hydrogen peroxide solution can be performed by preparing a test piece having a weight equivalent to 10 molded articles (15 mm × 15 mm × 0.2 mm) using a fluorocopolymer, placing the test piece and 15 g of a 3 mass% aqueous hydrogen peroxide solution in a polypropylene bottle in a constant temperature bath at 95°C and leaving it for 20 hours.

[0050] The fluorine-containing copolymer of the present disclosure can be produced by any of polymerization methods such as bulk polymerization, solution polymerization, suspension polymerization, emulsion polymerization, etc. In these polymerization methods, each condition such as temperature, pressure, polymerization initiator, chain transfer agent, solvent and other additives can be appropriately set according to the composition and amount of the desired fluorine-containing copolymer.

[0051] As the polymerization initiator, an oil-soluble radical polymerization initiator or a water-soluble radical initiator can be used.

[0052] The oil-soluble radical polymerization initiator may be a known oil-soluble peroxide, for example, dialkyl peroxycarbonates such as di-n-propyl peroxydicarbonate, diisopropyl peroxydicarbonate, and di-sec-butyl peroxydicarbonate; Peroxyesters such as t-butyl peroxyisobutyrate and t-butyl peroxypivalate; Dialkyl peroxides such as di-t-butyl peroxide; Di[fluoro(or fluorochloro)acyl]peroxides; The following are some representative examples.

[0053] Di[fluoro(or fluorochloro)acyl]peroxides include [(RfCOO)-] 2 (Rf is a perfluoroalkyl group, an ω-hydroperfluoroalkyl group, or a fluorochloroalkyl group).

[0054] Examples of di[fluoro(or fluorochloro)acyl]peroxides include di(ω-hydro-dodecafluorohexanoyl)peroxide, di(ω-hydro-tetradecafluoroheptanoyl)peroxide, di(ω-hydro-hexadecafluorononanoyl)peroxide, di(perfluorobutyryl)peroxide, di(perfluoroparyl)peroxide, di(perfluorohexanoyl)peroxide, di(perfluoroheptanoyl)peroxide, di(perfluorooctanoyl)peroxide, di(perfluorononanoyl)peroxide, di(ω-chloro-hexafluorobutyryl)peroxide, di(ω-chloro-decafluorohexanoyl)peroxide, Examples of the peroxide include di(ω-chloro-tetradecafluorooctanoyl) peroxide, ω-hydrodecafluoroheptanoyl-ω-hydrohexadecafluorononanoyl peroxide, ω-chlorohexafluorobutyryl-ω-chlorodecafluorohexanoyl peroxide, ω-hydrododecafluoroheptanoyl-perfluorobutyryl peroxide, di(dichloropentafluorobutanoyl) peroxide, di(trichlorooctafluorohexanoyl) peroxide, di(tetrachloroundecafluorooctanoyl) peroxide, di(pentachlorotetradecafluorodecanoyl) peroxide, and di(undecachlorotriacontafluorodocosanoyl) peroxide.

[0055] The water-soluble radical polymerization initiator may be a known water-soluble peroxide, such as ammonium salts, potassium salts, or sodium salts of persulfuric acid, perboric acid, perchloric acid, perphosphoric acid, or percarbonic acid, t-butyl permaleate, or t-butyl hydroperoxide, etc. A reducing agent such as a sulfite may also be contained, and the amount used may be 0.1 to 20 times that of the peroxide.

[0056] It is preferable to use an oil-soluble radical polymerization initiator as the polymerization initiator, since it is possible to avoid the generation of -COF and -COOH, and the total number of -COF and -COOH in the fluorine-containing copolymer can be easily adjusted to the above-mentioned range. 2 H, carbonyl-containing end group, -CF=CF 2 and -CH 2 The total number of OH groups tends to be easily adjusted to the above-mentioned range. In particular, it is preferable to produce a fluorine-containing copolymer by suspension polymerization using an oil-soluble radical polymerization initiator. As the oil-soluble radical polymerization initiator, at least one selected from the group consisting of dialkyl peroxycarbonates and di[fluoro (or fluorochloro) acyl] peroxides is preferable, and at least one selected from the group consisting of di-normal propyl peroxydicarbonate, diisopropyl peroxydicarbonate and di(ω-hydro-dodecafluoroheptanoyl) peroxide is more preferable.

[0057] Examples of the chain transfer agent include hydrocarbons such as ethane, isopentane, n-hexane, and cyclohexane; aromatics such as toluene and xylene; ketones such as acetone; acetates such as ethyl acetate and butyl acetate; alcohols such as methanol, ethanol, and 2,2,2-trifluoroethanol; mercaptans such as methyl mercaptan; halogenated hydrocarbons such as carbon tetrachloride, chloroform, methylene chloride, and methyl chloride; and 3-fluorobenzotrifluoride. The amount of the agent to be added may vary depending on the magnitude of the chain transfer constant of the compound used, but is usually used in the range of 0.01 to 20 parts by mass relative to 100 parts by mass of the solvent.

[0058] For example, when dialkyl peroxycarbonates, di[fluoro (or fluorochloro) acyl] peroxides, etc. are used as polymerization initiators, the molecular weight of the resulting fluorine-containing copolymer becomes too high, and it may not be easy to adjust the melt flow rate to a desired value, but the molecular weight can be adjusted using a chain transfer agent. In particular, it is preferable to produce the fluorine-containing copolymer by suspension polymerization using a chain transfer agent such as alcohols and an oil-soluble radical polymerization initiator.

[0059] Examples of the solvent include water, a mixed solvent of water and alcohol, etc. Furthermore, the monomer used in the polymerization of the fluorine-containing copolymer of the present disclosure can also be used as the solvent.

[0060] In the suspension polymerization, in addition to water, a fluorine-based solvent may be used. 3 CClF 2 , C.H. 3 CCl 2 F, C.F. 3 CF 2 CCl 2 H, C.F. 2 ClCF 2 Hydrochlorofluoroalkanes such as CFHCl; CF 2 ClCFClCF 2 CF 3 , C.F. 3 CFClCFClCF 3 Chlorofluoroalkanes such as perfluorocyclobutane, CF 3 CF 2 CF 2 CF 3 , C.F. 3 CF 2 CF 2 CF 2 CF 3 , C.F. 3 CF 2 CF 2 CF 2 CF 2 CF 3Among them, perfluoroalkanes are preferable. The amount of the fluorine-based solvent used is preferably 10 to 100 parts by mass per 100 parts by mass of the solvent, from the standpoints of suspension property and economic efficiency.

[0061] The polymerization temperature is not particularly limited and may be 0 to 100° C. When the polymerization initiator is a dialkyl peroxycarbonate, a di[fluoro (or fluorochloro) acyl] peroxide, or the like, and the decomposition rate of the polymerization initiator is too fast, it is preferable to adopt a relatively low polymerization temperature, such as a polymerization temperature in the range of 0 to 35° C.

[0062] The polymerization pressure is appropriately determined depending on other polymerization conditions such as the type of solvent used, the amount of the solvent, the vapor pressure, and the polymerization temperature, but may usually be 0 to 9.8 MPaG. The polymerization pressure is preferably 0.1 to 5 MPaG, more preferably 0.5 to 2 MPaG, and further preferably 0.5 to 1.5 MPaG. Furthermore, when the polymerization pressure is 1.5 MPaG or more, the production efficiency can be improved.

[0063] Additives in polymerization include, for example, suspension stabilizers. The suspension stabilizer is not particularly limited as long as it is a conventionally known one, and methyl cellulose, polyvinyl alcohol, etc. can be used. When a suspension stabilizer is used, the suspended particles generated by the polymerization reaction are stably dispersed in the aqueous medium, so that even if a SUS reaction tank that has not been treated for adhesion prevention such as glass lining is used, the suspended particles are unlikely to adhere to the reaction tank. Therefore, a reaction tank that can withstand high pressure can be used, making it possible to polymerize under high pressure and improving production efficiency. On the other hand, when polymerization is performed without using a suspension stabilizer, if a SUS reaction tank that has not been treated for adhesion prevention is used, there is a risk that the suspended particles will adhere and the production efficiency will decrease. The concentration of the suspension stabilizer relative to the aqueous medium can be appropriately adjusted depending on the conditions.

[0064] When an aqueous dispersion containing a fluoropolymer is obtained by polymerization reaction, the fluorocopolymer contained in the aqueous dispersion may be coagulated, washed, and dried to recover the dry fluoropolymer. When a fluorocopolymer is obtained as a slurry by polymerization reaction, the slurry may be taken out of the reaction vessel, washed, and dried to recover the dry fluoropolymer. By drying, the fluorocopolymer can be recovered in the form of a powder.

[0065] The fluorocopolymer obtained by polymerization may be molded into pellets. The molding method for molding into pellets is not particularly limited, and conventionally known methods can be used. For example, a method of melt-extruding the fluorocopolymer using a single-screw extruder, twin-screw extruder, or tandem extruder, cutting into a predetermined length, and molding into pellets can be mentioned. The extrusion temperature during melt extrusion must be changed depending on the melt viscosity of the fluorocopolymer and the production method, and is preferably from the melting point of the fluorocopolymer +20°C to the melting point of the fluorocopolymer +140°C. The cutting method of the fluorocopolymer is not particularly limited, and conventionally known methods such as a strand cut method, a hot cut method, an underwater cut method, and a sheet cut method can be adopted. The obtained pellets may be heated to remove volatiles in the pellets (degassing treatment). The obtained pellets may be treated by contacting them with hot water at 30 to 200°C, steam at 100 to 200°C, or hot air at 40 to 200°C.

[0066] The fluorocopolymer obtained by polymerization may be heated to a temperature of 100°C or higher in the presence of air and water (wet heat treatment). Examples of the wet heat treatment method include a method in which the fluorocopolymer obtained by polymerization is melted and extruded while supplying air and water using an extruder. By the wet heat treatment, thermally unstable functional groups such as -COF and -COOH of the fluorocopolymer are converted to relatively thermally stable -CF 2 H can be converted to fluorinated copolymer -CF 2 H, carbonyl-containing end group, -CF=CF 2 and -CH 2The total number of OH groups can be easily adjusted to the above-mentioned range. By heating the fluorocopolymer in the presence of an alkali metal salt in addition to air and water, -CF 2 It is possible to promote the conversion reaction to H. However, depending on the application of the fluorocopolymer, it should be noted that contamination with alkali metal salts should be avoided.

[0067] The fluorine-containing copolymer obtained by polymerization may be fluorinated. From the viewpoint of obtaining a molded article that is less likely to dissolve fluorine ions in a chemical solution such as hydrogen peroxide, it is preferable to fluorinate the fluorine-containing copolymer. The fluorination treatment can be carried out by contacting a fluorine-containing copolymer that has not been fluorinated with a fluorine-containing compound. The fluorination treatment converts -COOH, -COOCH 3 , -CH 2 OH, -COF, -CF=CF 2 , -CONH 2 and the relatively thermally stable -CF 2 H and other functional groups are converted to the thermally extremely stable -CF 3 As a result, the -CF of the fluorine-containing copolymer can be converted to 2 H, carbonyl-containing end group, -CF=CF 2 and -CH 2 The total number of OH groups can be easily adjusted to fall within the ranges given above.

[0068] The fluorine-containing compound is not particularly limited, but may be a fluorine radical source that generates fluorine radicals under fluorination treatment conditions. 2 Gas, CoF 3 , AgF 2 , U.F. 6 , OF 2 , N 2 F 2 , C.F. 3 OF, halogen fluorides (e.g. IF 5 , ClF 3 ) etc.

[0069] F 2The fluorine radical source such as gas may be of 100% concentration, but from the viewpoint of safety, it is preferable to mix with an inert gas and dilute it to 5 to 50 mass %, more preferably to dilute it to 15 to 30 mass %. Examples of the inert gas include nitrogen gas, helium gas, and argon gas, and nitrogen gas is preferable from the viewpoint of economy.

[0070] The conditions for the fluorination treatment are not particularly limited, and the fluorine-containing copolymer in a molten state may be contacted with the fluorine-containing compound, but the fluorination treatment is usually carried out at a temperature below the melting point of the fluorine-containing copolymer, preferably at 20 to 220°C, more preferably at 100 to 200°C. The fluorination treatment is generally carried out for 1 to 30 hours, preferably 5 to 25 hours. The fluorination treatment is carried out by subjecting a fluorine-containing copolymer that has not been fluorinated to fluorine gas (F 2 It is preferable to contact the gas with the

[0071] A composition may be obtained by mixing the fluorine-containing copolymer of the present disclosure with other components as necessary. Examples of other components include fillers, plasticizers, processing aids, release agents, pigments, flame retardants, lubricants, light stabilizers, weathering stabilizers, conductive agents, antistatic agents, UV absorbers, antioxidants, foaming agents, fragrances, oils, softening agents, dehydrofluorination agents, etc.

[0072] Examples of the filler include silica, kaolin, clay, organo clay, talc, mica, alumina, calcium carbonate, calcium terephthalate, titanium oxide, calcium phosphate, calcium fluoride, lithium fluoride, cross-linked polystyrene, potassium titanate, carbon, boron nitride, carbon nanotubes, and glass fibers. Examples of the conductive agent include carbon black. Examples of the plasticizer include dioctyl phthalate and pentaerythritol. Examples of the processing aid include carnauba wax, sulfone compounds, low molecular weight polyethylene, and fluorine-based aids. Examples of the dehydrofluorination agent include organic oniums and amidines.

[0073] As the other component, a polymer other than the above-mentioned fluorine-containing copolymer may be used. Examples of the other polymer include a fluororesin, a fluorine rubber, and a non-fluorinated polymer other than the above-mentioned fluorine-containing copolymer.

[0074] Examples of a method for producing the above composition include a method of dry mixing the fluorocopolymer and other components, and a method of previously mixing the fluorocopolymer and other components in a mixer and then melt-kneading them in a kneader, melt extruder or the like.

[0075] The fluorine-containing copolymer of the present disclosure or the above composition can be used as a processing aid, molding material, etc., but is preferably used as a molding material. In addition, aqueous dispersions, solutions, suspensions, and copolymer / solvent systems of the fluorine-containing copolymer of the present disclosure can also be used, and these can be applied as paints, or used for encapsulation, impregnation, and film casting. However, since the fluorine-containing copolymer of the present disclosure has the above-mentioned properties, it is preferably used as the above-mentioned molding material.

[0076] The fluorocopolymer of the present disclosure or the above composition may be molded to obtain a molded article.

[0077] The method for molding the fluorine-containing copolymer or the composition is not particularly limited, and includes injection molding, extrusion, compression, blow, transfer, roto-molding, roto-lining, etc. As the molding method, among them, extrusion, compression, injection or transfer molding is preferred, and injection, extrusion or transfer molding is more preferred, and injection molding is even more preferred, because it can produce a molded body with high productivity. That is, the molded body is preferably an extrusion molded body, a compression molded body, an injection molded body or a transfer molded body, and injection, extrusion or transfer molding is more preferred, because it can be produced with high productivity, and injection molding is even more preferred. By molding the fluorine-containing copolymer of the present disclosure by injection molding, a beautiful molded body can be obtained.

[0078] The molded article containing the fluorinated copolymer of the present disclosure may be, for example, a nut, a bolt, a joint, a film, a bottle, a gasket, an electric wire coating, a tube, a hose, a pipe, a valve, a sheet, a seal, a packing, a tank, a roller, a container, a cock, a connector, a filter housing, a filter cage, a flow meter, a pump, a wafer carrier, a wafer box, or the like.

[0079] The fluorocopolymer of the present disclosure, the above composition, or the above molded article can be used, for example, in the following applications. Food packaging films, lining materials for fluid transfer lines used in food manufacturing processes, packings, sealing materials, sheets and other fluid transfer components for food manufacturing equipment; Chemical stoppers, packaging films, lining materials for fluid transfer lines used in pharmaceutical manufacturing processes, packings, sealing materials, sheets and other chemical transfer components; Inner lining materials for chemical tanks and pipes in chemical plants and semiconductor factories; O-rings, tubes, packing, valve core materials, hoses, seals, etc. used in automobile fuel systems and peripheral devices; hoses, seals, and other fuel transfer materials used in automobile automatic transmission devices; Carburetor flange gaskets, shaft seals, valve stem seals, sealing materials, hoses, etc. used in automobile engines and peripheral devices, automobile brake hoses, air conditioner hoses, radiator hoses, electric wire covering materials, and other automobile parts; Semiconductor manufacturing equipment O-rings, tubes, packing, valve core materials, hoses, seal materials, rolls, gaskets, diaphragms, joints, and other chemical liquid transfer components for semiconductor equipment; Paint rolls for painting equipment, hoses, tubes, ink containers and other paint and ink components; Food and beverage tubes and food and beverage hoses and other food and beverage transport components such as tubes, hoses, belts, packings, and joints, food packaging materials, and glass cooking equipment; Waste liquid transport components such as tubes and hoses for transporting waste liquid; Components for transporting high-temperature liquids, such as tubes and hoses for transporting high-temperature liquids; Steam piping components such as steam piping tubes and hoses; Anticorrosive tapes for piping, such as tapes wrapped around piping on ship decks, etc.; Various coating materials such as electric wire coating materials, optical fiber coating materials, transparent front coating materials and back coating materials to be applied to the light incident surface of photovoltaic elements of solar cells; Sliding parts such as diaphragms in diaphragm pumps and various packings; Agricultural films, weather-resistant covers for various roofing materials and side walls; Interior materials used in the construction industry, and glass covering materials such as non-flammable fire-resistant safety glass; Lining materials such as laminated steel sheets used in the home appliance sector, etc.;

[0080] Further examples of the fuel transfer members used in the fuel systems of the above-mentioned automobiles include fuel hoses, filler hoses, evaporative hoses, etc. The above-mentioned fuel transfer members can also be used as fuel transfer members for sour gasoline, alcohol-resistant fuels, and fuels containing gasoline additives such as methyl tertiary butyl ether and amine-resistant fuels.

[0081] The above-mentioned chemical stoppers and packaging films for chemicals have excellent chemical resistance against acids, etc. Another example of the above-mentioned chemical liquid transfer member is anticorrosive tape wrapped around piping in chemical plants.

[0082] Examples of the molded article include radiator tanks for automobiles, chemical tanks, bellows, spacers, rollers, gasoline tanks, containers for transporting waste liquids, containers for transporting high-temperature liquids, and fishery / fish farming tanks.

[0083] Further examples of the molded article include parts used for automobile bumpers, door trims, instrument panels, food processing equipment, cooking appliances, water- and oil-repellent glass, lighting-related equipment, display panels and housings for office automation equipment, illuminated signs, displays, liquid crystal displays, mobile phones, printed circuit boards, electric and electronic components, miscellaneous goods, trash cans, bathtubs, unit baths, ventilation fans, lighting frames, etc.

[0084] A molded article containing the fluorocopolymer of the present disclosure has excellent abrasion resistance at 140°C, ozone resistance, heat aging resistance, water vapor permeability, low oxygen permeability, rigidity at a high temperature of 100°C, tensile creep resistance at 110°C and extrusion moldability, and can therefore be suitably used for containers, tubes, films, wire coatings, etc.

[0085] A molded article containing the fluorocopolymer of the present disclosure can be suitably used as a compressed member such as a gasket, packing, etc. The compressed member of the present disclosure may be a gasket or a packing.

[0086] The size and shape of the compressed member of the present disclosure may be appropriately set depending on the application, and are not particularly limited. The shape of the compressed member of the present disclosure may be, for example, annular. In addition, the compressed member of the present disclosure may have a shape such as a circle, an oval, or a rectangle with rounded corners in a plan view, and may have a through hole in the center.

[0087] The compressed member of the present disclosure is preferably used as a member for constituting a nonaqueous electrolyte battery. The compressed member of the present disclosure is particularly suitable as a member used in a state in which it is in contact with the nonaqueous electrolyte in the nonaqueous electrolyte battery. That is, the compressed member of the present disclosure may have a surface in contact with the nonaqueous electrolyte in the nonaqueous electrolyte battery.

[0088] The nonaqueous electrolyte battery is not particularly limited as long as it is a battery containing a nonaqueous electrolyte, and examples thereof include a lithium ion secondary battery, a lithium ion capacitor, etc. Examples of members constituting the nonaqueous electrolyte battery include a sealing member, an insulating member, etc.

[0089] The non-aqueous electrolyte is not particularly limited, but one or more of known solvents such as propylene carbonate, ethylene carbonate, butylene carbonate, γ-butyl lactone, 1,2-dimethoxyethane, 1,2-diethoxyethane, dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate can be used. The non-aqueous electrolyte battery may further include an electrolyte. The electrolyte is not particularly limited, but may be LiClO 4 , LiAsF 6 , LiPF 6 , LiBF 4 , LiCl, LiBr, CH 3 SO 3 Li, C.F. 3 SO 3 Li, cesium carbonate, etc. can be used.

[0090] The compressed member of the present disclosure can be suitably used as, for example, a sealing member such as a sealing gasket or sealing packing, or an insulating member such as an insulating gasket or insulating packing. A sealing member is a member used to prevent leakage of liquid or gas or intrusion of liquid or gas from the outside. An insulating member is a member used to insulate electricity. The compressed member of the present disclosure may be a member used for both sealing and insulating purposes.

[0091] The compressed member of the present disclosure can be suitably used as a sealing member for a non-aqueous electrolyte battery or an insulating member for a non-aqueous electrolyte battery. In addition, since the compressed member of the present disclosure contains the above-mentioned fluorine-containing copolymer, it has excellent insulating properties. Therefore, when the compressed member of the present disclosure is used as an insulating member, it firmly adheres to two or more conductive members and prevents short circuits for a long period of time.

[0092] The fluorocopolymer of the present disclosure can be suitably used as a material for forming an electric wire coating. A coated electric wire having a coating layer containing the fluorocopolymer of the present disclosure has excellent electrical properties since there is almost no variation in the outer diameter.

[0093] The coated electric wire comprises a core wire and a coating layer that is provided around the core wire and contains the fluorocopolymer of the present disclosure. For example, the coating layer can be an extrusion molded body obtained by melt-extrusion molding the fluorocopolymer of the present disclosure onto the core wire. The coated electric wire is suitable for LAN cables (Ethernet Cables), high-frequency transmission cables, flat cables, heat-resistant cables, etc., and is particularly suitable for transmission cables such as LAN cables (Ethernet Cables) and high-frequency transmission cables.

[0094] The core wire may be made of a metal conductor material such as copper or aluminum. The core wire preferably has a diameter of 0.02 to 3 mm. The core wire preferably has a diameter of 0.04 mm or more, more preferably 0.05 mm or more, and particularly preferably 0.1 mm or more. The core wire preferably has a diameter of 2 mm or less.

[0095] Specific examples of the core wire include AWG (American Wire Gauge)-46 (solid copper wire with a diameter of 40 micrometers), AWG-26 (solid copper wire with a diameter of 404 micrometers), AWG-24 (solid copper wire with a diameter of 510 micrometers), and AWG-22 (solid copper wire with a diameter of 635 micrometers).

[0096] The thickness of the coating layer is preferably 0.1 to 3.0 mm. It is also preferable that the thickness of the coating layer is 2.0 mm or less.

[0097] An example of a high-frequency transmission cable is a coaxial cable. A coaxial cable generally has a structure in which an internal conductor, an insulating coating layer, an external conductor layer, and a protective coating layer are laminated in this order from the core to the outer periphery. A molded article containing the fluorine-containing copolymer of the present disclosure can be suitably used as an insulating coating layer containing a fluorine-containing copolymer. The thickness of each layer in the above structure is not particularly limited, but usually, the internal conductor has a diameter of about 0.1 to 3 mm, the insulating coating layer has a thickness of about 0.3 to 3 mm, the external conductor layer has a thickness of about 0.5 to 10 mm, and the protective coating layer has a thickness of about 0.5 to 2 mm.

[0098] The coating layer may contain air bubbles, and it is preferable that the air bubbles are uniformly distributed in the coating layer.

[0099] The average bubble diameter of the bubbles is not limited, but is preferably 60 μm or less, more preferably 45 μm or less, even more preferably 35 μm or less, even more preferably 30 μm or less, particularly preferably 25 μm or less, and even more preferably 23 μm or less. The average bubble diameter is preferably 0.1 μm or more, and more preferably 1 μm or more. The average bubble diameter can be determined by taking an electron microscope image of the cross section of the electric wire, calculating the diameter of each bubble by image processing, and averaging the results.

[0100] The coating layer may have an expansion rate of 20% or more. More preferably, it is 30% or more, even more preferably, it is 33% or more, and even more preferably, it is 35% or more. There is no particular upper limit, but it is, for example, 80%. The upper limit of the expansion rate may be 60%. The expansion rate is a value calculated by ((specific gravity of electric wire coating material-specific gravity of coating layer) / specific gravity of electric wire coating material)×100. The expansion rate can be appropriately adjusted according to the application, for example, by adjusting the amount of gas inserted in the extruder described later, or by selecting the type of gas to be dissolved.

[0101] The coated electric wire may have another layer between the core wire and the coating layer, or may have another layer (outer layer) around the coating layer. When the coating layer contains bubbles, the electric wire of the present disclosure may have a two-layer structure (skin-foam) in which a non-foamed layer is inserted between the core wire and the coating layer, a two-layer structure (foam-skin) in which the outer layer is coated with a non-foamed layer, or even a three-layer structure (skin-foam-skin) in which the outer layer of skin-foam is coated with a non-foamed layer. The non-foamed layer is not particularly limited, and may be a resin layer made of a resin such as a TFE / HFP copolymer, a TFE / PAVE copolymer, a TFE / ethylene copolymer, a vinylidene fluoride polymer, a polyolefin resin such as polyethylene (PE), or polyvinyl chloride (PVC).

[0102] The covered electric wire can be produced, for example, by heating the fluorocopolymer using an extruder and extruding the fluorocopolymer in a molten state onto a core wire to form a covering layer.

[0103] When forming the coating layer, the fluorocopolymer is heated and in a molten state, a gas is introduced into the fluorocopolymer to form the coating layer containing bubbles. As the gas, for example, gas such as chlorodifluoromethane, nitrogen, carbon dioxide, etc., or a mixture of the above gases can be used. The gas may be introduced into the heated fluorocopolymer as a pressurized gas, or may be generated by mixing a chemical foaming agent into the fluorocopolymer. The gas dissolves in the molten fluorocopolymer.

[0104] Furthermore, the fluorine-containing copolymer of the present disclosure can be suitably used as a material for high-frequency signal transmission products.

[0105] The above-mentioned high-frequency signal transmission products are not particularly limited as long as they are products used for transmitting high-frequency signals, and examples thereof include (1) insulating plates for high-frequency circuits, insulators for connecting parts, molded plates such as printed wiring boards, (2) molded bodies such as bases for high-frequency vacuum tubes and antenna covers, and (3) coated electric wires such as coaxial cables and LAN cables. The above-mentioned high-frequency signal transmission products can be suitably used in devices that utilize microwaves, particularly microwaves of 3 to 30 GHz, such as satellite communication devices and mobile phone base stations.

[0106] In the above-mentioned high-frequency signal transmission product, the fluorine-containing copolymer of the present disclosure can be suitably used as an insulator because of its low dielectric tangent.

[0107] The above (1) molded plate is preferably a printed wiring board in that it can obtain good electrical properties. The above printed wiring board is not particularly limited, but examples thereof include printed wiring boards for electronic circuits of mobile phones, various computers, communication devices, etc. The above (2) molded body is preferably an antenna cover in that it has low dielectric loss.

[0108] The fluorine-containing copolymer of the present disclosure can be suitably used for a film.

[0109] The film of the present disclosure is useful as a release film. The release film can be produced by molding the fluorocopolymer of the present disclosure by melt extrusion molding, calendar molding, press molding, casting molding, etc. From the viewpoint of obtaining a uniform thin film, the release film can be produced by melt extrusion molding.

[0110] The film of the present disclosure can be applied to the surface of rolls used in OA equipment. The fluorocopolymer of the present disclosure can be molded into a required shape by extrusion molding, compression molding, press molding, etc., to form a sheet, film, or tube, and can be used as a surface material for OA equipment rolls or OA equipment belts, etc. In particular, thin-walled tubes and films can be produced by melt extrusion molding.

[0111] The fluorine-containing copolymer of the present disclosure can also be suitably used for tubes, bottles, and the like.

[0112] Although the embodiments have been described above, it will be understood that various changes in form and details are possible without departing from the spirit and scope of the claims. EXAMPLES

[0113] Next, embodiments of the present disclosure will be described with reference to examples, but the present disclosure is not limited to these examples.

[0114] The values ​​in the examples were measured by the following methods.

[0115] (Monomer unit content) The content of each monomer unit in the fluorocopolymer was measured using an NMR analyzer (for example, AVANCE300 high temperature probe manufactured by Bruker Biospin) or an infrared absorption analyzer (Spectrum One manufactured by PerkinElmer).

[0116] (Melt Flow Rate (MFR)) The MFR of the fluorocopolymer was determined in accordance with ASTM D-1238 by measuring the mass (g / 10 min) of the polymer flowing out from a die having an inner diameter of 2 mm and a length of 8 mm at 372°C under a load of 5 kg per 10 min using a Melt Indexer G-01 (manufactured by Toyo Seiki Seisakusho).

[0117] (-CF 2 Number of H) Fluorine-containing copolymer -CF 2 The number of H groups was measured using a nuclear magnetic resonance spectrometer AVANCE-300 (manufactured by Bruker Biospin) at a measurement temperature of (polymer melting point + 20)°C. 19 F-NMR measurement was performed using -CF 2 It was calculated from the peak integral value of H group.

[0118] (-COOH, -COOCH 3 , -CH 2 OH, -COF, -CF=CF 2 , -CONH 2 (Number of The dry powders or pellets obtained in the examples and comparative examples were molded by cold pressing to prepare films with a thickness of 0.25 to 0.3 mm. The films were scanned 40 times using a Fourier transform infrared spectrometer [FT-IR (Spectrum One, manufactured by PerkinElmer)] to analyze and obtain infrared absorption spectra. The obtained infrared absorption spectrum was compared with the infrared absorption spectrum of a known film to determine the type of terminal group. In addition, the absorption peak of a specific functional group appearing in the difference spectrum between the obtained infrared absorption spectrum and the infrared absorption spectrum of a known film was used to determine the number of carbon atoms in the sample per 1×10 according to the following formula (A): 6The number of functional groups per unit, N, was calculated.

[0119] N=I×K / t (A) I: Absorbance K: Correction coefficient t: film thickness (mm)

[0120] For reference, the absorption frequencies, molar absorption coefficients, and correction coefficients for the functional groups in the examples are shown in Table 2. The molar absorption coefficients were determined from the FT-IR measurement data of low molecular weight model compounds.

[0121] [Table 2]

[0122] (Number of -OC(=O)OR (carbonate groups)) The analysis was performed according to the method described in International Publication No. 2019 / 220850. The absorption frequency was 1817 cm -1 The number of -OC(=O)OR (carbonate groups) was calculated in the same manner as for the number of functional groups N, except that the molar absorbance coefficient was 170 (l / cm / mol) and the correction factor was 1426.

[0123] (Melting Point) The melting point of the fluorocopolymer was determined using a differential scanning calorimeter (product name: X-DSC7000, manufactured by Hitachi High-Tech Science Corporation) by first heating from 200°C to 350°C at a heating rate of 10°C / min, subsequently cooling from 350°C to 200°C at a cooling rate of 10°C / min, and then heating a second time from 200°C to 350°C at a heating rate of 10°C / min, and determining the melting point from the peak of the melting curve occurring during the second heating process.

[0124] Comparative Example 1 945g of deionized water and 8.7g of methanol were put into a 4L autoclave equipped with a stirrer, and the inside of the autoclave was thoroughly evacuated and replaced with nitrogen. After that, the inside of the autoclave was evacuated and 945g of HFP and 13.9g of PEVE were put into the vacuumed autoclave, and the autoclave was heated to 30.0°C. TFE was then put in until the internal pressure of the autoclave reached 0.929MPa, and then 14.7g of 8% by mass of di(ω-hydroperfluorohexanoyl) peroxide solution (hereinafter abbreviated as DHP) was put into the autoclave to start polymerization. The internal pressure of the autoclave at the start of polymerization was set to 0.929MPa, and the set pressure was maintained by continuously adding TFE. 1.5 hours after the start of polymerization, 8.7g of methanol was added. Two and four hours after the start of polymerization, 14.7 g of DHP was added and the internal pressure was reduced by 0.001 MPa, and 6 hours later, 11.3 g was added and the internal pressure was reduced by 0.001 MPa. After that, 3.0 g of DHP was added every two hours, and the internal pressure was reduced by 0.001 MPa each time until the reaction was completed.

[0125] In addition, 3.9 g of PEVE was added when the amount of TFE added continuously reached 190 g and 380 g, respectively. In addition, 8.7 g of methanol was added to the autoclave when the amount of TFE added reached 140 g. Then, the polymerization was terminated when the amount of TFE added reached 454 g. After the polymerization was completed, the unreacted TFE and HFP were discharged to obtain a wet powder. Then, this wet powder was washed with pure water and dried at 150°C for 10 hours to obtain 519 g of dry powder.

[0126] The obtained powder was melt-extruded at 370°C using a 14φ screw extruder (manufactured by Imoto Seisakusho) to obtain pellets of the copolymer. The HFP content and PEVE content of the obtained pellets were measured by the above-mentioned method. The results are shown in Table 3.

[0127] The obtained pellets were degassed in an electric furnace at 200° C. for 8 hours, then placed in a portable reactor TVS1 type (manufactured by Taiatsu Glass Industries Co., Ltd.) and heated to 200° C. After evacuation, N2 F diluted with gas to 20% by volume 2 Gas was introduced up to atmospheric pressure. 2 0.5 hours after gas introduction, vacuum was drawn once and F was again 2 After another 0.5 hours, the vacuum was pulled again and F gas was introduced. 2 Gas was introduced. 2 The gas introduction and evacuation were carried out once every hour, and the reaction was carried out at 200°C for 8 hours. After the reaction was completed, the inside of the reactor was filled with N 2 The atmosphere was replaced with gas sufficiently to terminate the fluorination reaction, and pellets were obtained. The pellets obtained were used to measure various physical properties by the methods described above. The results are shown in Table 3.

[0128] Comparative Example 2 The amount of methanol added before the start of polymerization was changed to 6.6 g, the amount of methanol added in portions after the start of polymerization was changed to 6.6 g, the amount of PEVE added before the start of polymerization was changed to 15.5 g, the amount of PEVE added in portions after the start of polymerization was changed to 4.7 g, and the pressure set inside the autoclave before and after the start of polymerization was changed to 0.912 MPa. Copolymer pellets were obtained in the same manner as in Comparative Example 1. The HFP content and PEVE content were measured by the above-mentioned method using the obtained pellets. The results are shown in Table 3.

[0129] The obtained pellets were fluorinated in the same manner as in Comparative Example 1. The obtained pellets were used to measure various physical properties by the methods described above. The results are shown in Table 3.

[0130] Comparative Example 3 The amount of methanol added before the start of polymerization was changed to 7.8 g, the amount of methanol added in portions after the start of polymerization was changed to 7.8 g, the amount of PEVE added before the start of polymerization was changed to 13.9 g, the amount of PEVE added in portions after the start of polymerization was changed to 4.4 g, and the pressure set inside the autoclave before and after the start of polymerization was changed to 0.900 MPa. Copolymer pellets were obtained in the same manner as in Comparative Example 1. The HFP content and PEVE content were measured by the above-mentioned method using the obtained pellets. The results are shown in Table 3.

[0131] The obtained pellets were fluorinated in the same manner as in Comparative Example 1. The obtained pellets were used to measure various physical properties by the methods described above. The results are shown in Table 3.

[0132] Comparative Example 4 The amount of methanol added before the start of polymerization was changed to 5.1 g, the amount of methanol added in portions after the start of polymerization was changed to 5.1 g, the amount of PEVE added before the start of polymerization was changed to 13.1 g, the amount of PEVE added in portions after the start of polymerization was changed to 4.4 g, and the pressure setting inside the autoclave before and after the start of polymerization was changed to 0.888 MPa. Copolymer pellets were obtained in the same manner as in Comparative Example 1. The HFP content and PEVE content were measured by the above-mentioned method using the obtained pellets. The results are shown in Table 3.

[0133] The obtained pellets were fluorinated in the same manner as in Comparative Example 1. The obtained pellets were used to measure various physical properties by the methods described above. The results are shown in Table 3.

[0134] Comparative Example 5 The amount of methanol added before the start of polymerization was changed to 9.8 g, the amount of methanol added in portions after the start of polymerization was changed to 9.8 g each, the addition of PEVE before and after the start of polymerization was eliminated, and the pressure inside the autoclave before and after the start of polymerization was changed to 0.909 MPa. Except for this, copolymer pellets were obtained in the same manner as in Comparative Example 1. The HFP content and PEVE content were measured by the above-mentioned method using the obtained pellets. The results are shown in Table 3.

[0135] The obtained pellets were fluorinated in the same manner as in Comparative Example 1. The obtained pellets were used to measure various physical properties by the methods described above. The results are shown in Table 3.

[0136] Comparative Example 6 40.25 kg of deionized water and 0.278 kg of methanol were put into a 174 L volume autoclave equipped with a stirrer, and the inside of the autoclave was thoroughly evacuated and replaced with nitrogen. After that, the inside of the autoclave was evacuated and 40.25 kg of HFP and 0.52 kg of PPVE were put into the evacuated autoclave, and the autoclave was heated to 30.0 ° C. Then, TFE was put in until the internal pressure of the autoclave reached 0.897 MPa, and then 0.63 kg of 8 mass% di(ω-hydroperfluorohexanoyl) peroxide solution (hereinafter abbreviated as DHP) was put into the autoclave to start polymerization. The internal pressure of the autoclave at the start of polymerization was set to 0.897 MPa, and the set pressure was maintained by continuously adding TFE. 1.5 hours after the start of polymerization, 0.278 kg of methanol was added. Two and four hours after the start of polymerization, 0.63 kg of DHP was added and the internal pressure was reduced by 0.001 MPa, and 6 hours later, 0.48 kg was added and the internal pressure was reduced by 0.001 MPa. After that, 0.13 kg of DHP was added every two hours until the reaction was completed, and the internal pressure was reduced by 0.001 MPa each time.

[0137] In addition, 0.17 kg of PPVE was added when the continuous additional amount of TFE reached 8.1 kg, 16.2 kg, and 24.3 kg, respectively. In addition, 0.278 kg of methanol was added to the autoclave when the additional amount of TFE reached 6.0 kg and 18.1 kg, respectively. Then, the polymerization was terminated when the additional amount of TFE reached 40.25 kg. After the polymerization was completed, the unreacted TFE and HFP were discharged to obtain a wet powder. Then, this wet powder was washed with pure water and dried at 150 ° C for 10 hours to obtain 46.7 kg of dry powder.

[0138] The obtained powder was melt-extruded at 370°C using a screw extruder (product name: PCM46, manufactured by Ikegai Co., Ltd.) to obtain pellets of the copolymer. The HFP content and PPVE content of the obtained pellets were measured by the above-mentioned method. The results are shown in Table 3.

[0139] The obtained pellets were degassed in an electric furnace at 200° C. for 8 hours, then placed in a vacuum vibration reactor VVD-30 (manufactured by Okawara Manufacturing Co., Ltd.) and heated to 200° C. After evacuation, N 2 F diluted to 20% by volume with gas 2 Gas was introduced up to atmospheric pressure. 2 0.5 hours after gas introduction, vacuum was drawn once and F was again 2 After another 0.5 hours, the vacuum was pulled again and F gas was introduced. 2 Gas was introduced. 2 The gas introduction and evacuation were carried out once every hour, and the reaction was carried out at 200°C for 8 hours. After the reaction was completed, the inside of the reactor was filled with N 2 The atmosphere was replaced with gas sufficiently to terminate the fluorination reaction, and pellets were obtained. The pellets obtained were used to measure various physical properties by the methods described above. The results are shown in Table 3.

[0140] Comparative Example 7 A dry powder was obtained in the same manner as in Comparative Example 1, except that the amount of methanol added before the start of polymerization was changed to 7.3 g, the amount of methanol added in separate installments after the start of polymerization was changed to 7.3 g each, the amount of PEVE added before the start of polymerization was changed to 15.9 g, the amount of PEVE added in separate installments after the start of polymerization was changed to 4.7 g each, and the set pressure inside the autoclave before and after the start of polymerization was changed to 0.917 MPa.

[0141] The obtained powder was melt-extruded at 395°C using a 14φ screw extruder (manufactured by Imoto Seisakusho) to obtain pellets of the copolymer. The HFP content and PEVE content of the obtained pellets were measured by the above-mentioned method. The results are shown in Table 3.

[0142] Immediately after extrusion pelletization, the obtained pellets were heated in a hot air electric furnace at 120°C for 10 minutes, and then immediately placed in a portable reactor TVS1 type (manufactured by Taiatsu Glass Industries Co., Ltd.) and sealed. The reactor was then heated to 120°C. After evacuation, N 2 F diluted to 20% by volume with gas 2 Gas was introduced up to atmospheric pressure. 2 0.5 hours after gas introduction, vacuum was drawn once and F was again 2 After another 0.5 hours, the vacuum was pulled again and F gas was introduced. 2 Gas was introduced. 2 The gas introduction and evacuation were carried out once every hour, and the reaction was carried out at 120°C for 10 hours. After the reaction was completed, the inside of the reactor was filled with N 2 The atmosphere was replaced with gas sufficiently to terminate the fluorination reaction, and pellets were obtained. The pellets obtained were used to measure various physical properties by the methods described above. The results are shown in Table 3.

[0143] Example 1 The amount of methanol added before the start of polymerization was changed to 7.7 g, the amount of methanol added in portions after the start of polymerization was changed to 7.7 g each, the addition of PEVE before and after the start of polymerization was eliminated, and the pressure inside the autoclave before and after the start of polymerization was changed to 0.917 MPa. Except for this, copolymer pellets were obtained in the same manner as in Comparative Example 1. The HFP content and PEVE content were measured by the above-mentioned method using the obtained pellets. The results are shown in Table 3.

[0144] The obtained pellets were fluorinated in the same manner as in Comparative Example 1. The obtained pellets were used to measure various physical properties by the methods described above. The results are shown in Table 3.

[0145] Example 2 The amount of methanol added before the start of polymerization was changed to 7.2 g, the amount of methanol added in portions after the start of polymerization was changed to 7.2 g each, the addition of PEVE before and after the start of polymerization was eliminated, and the pressure setting inside the autoclave before and after the start of polymerization was changed to 0.909 MPa. Except for this, copolymer pellets were obtained in the same manner as in Comparative Example 1. The HFP content and PEVE content were measured by the above-mentioned method using the obtained pellets. The results are shown in Table 3.

[0146] The obtained pellets were fluorinated in the same manner as in Comparative Example 1. The obtained pellets were used to measure various physical properties by the methods described above. The results are shown in Table 3.

[0147] Example 3 The amount of methanol added before the start of polymerization was changed to 7.2 g, the amount of methanol added in portions after the start of polymerization was changed to 7.2 g each, the addition of PEVE before and after the start of polymerization was eliminated, and the pressure inside the autoclave before and after the start of polymerization was changed to 0.903 MPa. Except for this, copolymer pellets were obtained in the same manner as in Comparative Example 1. The HFP content and PEVE content were measured by the above-mentioned method using the obtained pellets. The results are shown in Table 3.

[0148] The obtained pellets were fluorinated in the same manner as in Comparative Example 1. The obtained pellets were used to measure various physical properties by the methods described above. The results are shown in Table 3.

[0149] Example 4 The amount of methanol added before the start of polymerization was changed to 6.1 g, the amount of methanol added in portions after the start of polymerization was changed to 6.1 g, the addition of PEVE before and after the start of polymerization was eliminated, and the pressure inside the autoclave before and after the start of polymerization was changed to 0.900 MPa. Except for this, copolymer pellets were obtained in the same manner as in Comparative Example 1. The HFP content and PEVE content were measured by the above-mentioned method using the obtained pellets. The results are shown in Table 3.

[0150] The obtained pellets were fluorinated in the same manner as in Comparative Example 1. The obtained pellets were used to measure various physical properties by the methods described above. The results are shown in Table 3.

[0151] [Table 3]

[0152] In Table 3, "Other (pieces / C10 6 )" is -COOCH 3 , -CF=CF 2 and -CONH 2 In Table 3, "<9" indicates the total number of -CF 2 It means that the number (total number) of H groups is less than 9. The notation "<6" in Table 3 means that the number (total number) of the target functional groups is less than 6. The notation "ND" in Table 3 means that no quantifiable peak was confirmed for the target functional group.

[0153] The pellets thus obtained were then used to evaluate the following properties, the results of which are shown in Table 4.

[0154] (Wear test) Using pellets and a heat press molding machine, a sheet-like test piece with a thickness of about 0.2 mm was prepared, and a test piece of 10 cm x 10 cm was cut out from it. The prepared test piece was fixed on the test stand of a Taber abrasion tester (No. 101 special type Taber abrasion tester, manufactured by Yasuda Seiki Seisakusho Co., Ltd.), and an abrasion test was performed using the Taber abrasion tester under the following conditions: test piece surface temperature 140°C, load 500 g, abrasion wheel CS-10 (polished 20 times with abrasive paper #240), and rotation speed 60 rpm. The weight of the test piece after 1000 rotations was measured, and the same test piece was further tested for 5000 rotations and then the weight of the test piece was measured. The amount of abrasion was calculated using the following formula. Wear amount (mg)=M1-M2 M1: Test piece weight after 1000 rotations (mg) M2: Test piece weight after 5000 rotations (mg)

[0155] (Ozone exposure test) The fluorocopolymer was compression molded at 350°C under a pressure of 0.5 MPa to prepare a sheet with a thickness of 1 mm, which was then cut into a size of 10 x 20 mm to prepare a sample for ozone exposure testing. Ozone gas (ozone / oxygen = 10 / 90% by volume) generated by an ozone generator (product name: SGX-A11MN (modified), manufactured by Sumitomo Seiki Kogyo Co., Ltd.) was connected to a PFA container containing ion-exchanged water, and water vapor was added to the ozone gas by bubbling it into the ion-exchanged water, and the sample was exposed to the wet ozone gas by passing it through a PFA cell containing the sample at room temperature at a rate of 0.7 liters / min. 60 days after the start of exposure, the sample was removed, the surface was lightly rinsed with ion-exchanged water, and the area 5 to 200 μm deep from the sample surface was observed at a magnification of 100 times using a transmission optical microscope, photographed with a standard scale, and the area 1 mm deep from the sample surface was measured. 2 The number of cracks with a length of 10 μm or more per unit area was measured. The evaluation was carried out according to the following criteria. ○: 10 or less cracks ×: More than 10 cracks

[0156] (Hot air crack test) Using pellets and a heat press molding machine, a sheet-like molded body with a thickness of about 2 mm was produced. The obtained sheet was punched out using a rectangular dumbbell of 13.5 mm x 38 mm to obtain three test pieces. A notch was made in the center of the long side of each of the obtained test pieces with a blade of 19 mm x 0.45 mm in accordance with ASTM D1693. Hot air at 120 ° C was applied to the three notched test pieces for 20 hours. The three obtained notched test pieces were attached to a stress crack test jig in accordance with ASTM D1693 and heated in an electric furnace at 120 ° C for 24 hours, after which the notch and its surroundings were visually observed and the number of cracks was counted. A sheet without cracks has excellent heat aging resistance. ○: The number of cracks is 0 ×: The number of cracks is 1 or more.

[0157] (Water vapor permeability) Using the pellets and a heat press molding machine, a sheet-like test piece with a thickness of about 0.2 mm was prepared. The test cup (permeation area 12.56 cm2) was 2 The sheet test piece was placed in a container containing 18 g of water, covered with a sheet test piece, and then clamped with a PTFE gasket to seal. The sheet test piece was placed in contact with the water and held at 95°C for 60 days, then removed and left at room temperature for 2 hours before measuring the amount of mass loss. The water vapor permeability (g cm / m 2 ) was measured. Water vapor permeability (g cm / m 2 ) = mass loss (g) × thickness of sheet specimen (cm) / permeation area (m 2 )

[0158] (Oxygen permeability coefficient) Using the pellets and a heat press molding machine, a sheet-like test piece with a thickness of about 0.1 mm was produced. The obtained test piece was used to measure the oxygen permeability using a differential pressure gas permeability meter (L100-5000 gas permeability meter, manufactured by Systech Illinois) according to the method described in JIS K7126-1:2006. Permeability area: 50.24 cm 2 The oxygen permeability was measured at a test temperature of 70°C and a test humidity of 0% RH. The oxygen permeability coefficient was calculated from the obtained oxygen permeability and the thickness of the test piece according to the following formula. Oxygen permeability coefficient (cm 3 mm / (m 2 ·24h·atm))=GTR×d GTR: Oxygen permeability (cm 3 / (m 2 24h atm) d: test piece thickness (mm)

[0159] (100℃ load deflection rate) Using pellets and a heat press molding machine, a sheet-like test piece with a thickness of about 4.2 mm was prepared, from which a test piece of 80 x 10 mm was cut out and heated in an electric furnace at 100 ° C for 20 hours. Except for using the obtained test piece, a test was performed in accordance with the method described in JIS KK 7191-1 using a heat distortion tester (manufactured by Yasuda Seiki Seisakusho Co., Ltd.) under the conditions of a test temperature of 30 to 150 ° C, a heating rate of 120 ° C / hour, a bending stress of 1.8 MPa, and a flatwise method. The deflection rate under load was calculated using the following formula. A sheet with a small deflection rate under load at 100 ° C has excellent rigidity at a high temperature of 100 ° C. Load deflection rate (%) = a2 / a1 x 100 a1: thickness of test piece before test (mm) a2: Deflection at 100℃ (mm)

[0160] (Tensile creep test) Tensile creep strain was measured using a Hitachi High-Tech Science TMA-7100. A sheet with a thickness of approximately 0.1 mm was produced using pellets and a heat press molding machine, and a sample with a width of 2 mm and a length of 22 mm was produced from the sheet. The sample was attached to a measuring jig with a jig distance of 10 mm. The cross-sectional load on the sample was 4.49 N / mm 2 A load was applied so that the sample would not stretch even when a tensile load was applied for a long period of time in a high-temperature environment, and the sample was left at 110°C. The sample's length displacement (mm) was measured from 90 minutes after the start of the test to 900 minutes after the start of the test, and the ratio of the length displacement (mm) to the initial sample length (10 mm) (tensile creep strain (%)) was calculated. Sheets with a small tensile creep strain (%) measured under conditions of 110°C and 900 minutes are less likely to stretch even when a tensile load is applied for a long period of time in a high-temperature environment, and have excellent high-temperature tensile creep resistance (110°C).

[0161] (Extrusion pressure) The extrusion pressure was measured using a twin capillary rheometer RHEOGRAPH 25 (manufactured by Goettfert). The main die had an inner diameter of 1 mm, L / D=16, and the sub-die had an inner diameter of 1 mm, L / D<1. The measurement temperature was 286°C, the preheating time after pellet introduction was 10 minutes, and the shear rate was 20 seconds. -1 The extrusion pressure was determined by Burgley correction of the pressure inside the cylinder after extrusion for 10 minutes at 1000 rpm. Copolymers with low extrusion pressure have excellent moldability, such as extrusion moldability and injection moldability.

[0162] (Hydrogen peroxide immersion test) Using pellets and a heat press molding machine, a sheet with a thickness of about 0.2 mm was prepared, and a test piece with a size of 15 mm square was prepared. 10 test pieces and 15 g of 3 mass% hydrogen peroxide solution were placed in a 50 mL polypropylene bottle, heated in an electric furnace at 95 ° C for 20 hours, and then cooled to room temperature. The test piece was removed from the hydrogen peroxide solution, and TISAB solution (10) (Kanto Chemical Co., Ltd.) was added to the remaining hydrogen peroxide solution, and the fluorine ion concentration in the resulting hydrogen peroxide solution was measured with a fluorine ion meter. From the measured values ​​obtained, the fluorine ion concentration per sheet weight (dissolved fluorine ion concentration) was calculated according to the following formula. Dissolved fluoride ion concentration (mass ppm) = measured value (ppm) × amount of hydrogen peroxide solution (g) / weight of test piece (g)

[0163] [Table 4]

Claims

1. A fluorine-containing copolymer containing tetrafluoroethylene units, hexafluoropropylene units and perfluoro(ethyl vinyl ether) units, The content of hexafluoropropylene units is 10.7 to 11.6 mass% based on the total monomer units, The content of perfluoro(ethyl vinyl ether) units is 1.2 to 2.4 mass% based on the total monomer units; The content of tetrafluoroethylene units is 86.0 to 88.1 mass% based on the total monomer units, The melt flow rate at 372°C is 28.0 to 40.0 g / 10 min. -CF 2 H, carbonyl-containing end group, -CF=CF 2 and -CH 2 The total number of OH groups is 10 6 Each piece is 21 or less. Fluorine-containing copolymer.

2. 2. The fluorine-containing copolymer according to claim 1, wherein the content of the hexafluoropropylene unit is 10.7 to 11.5 mass % based on the total monomer units.

3. 3. The fluorine-containing copolymer according to claim 1, wherein the content of perfluoro(ethyl vinyl ether) units is 1.4 to 1.8 mass % based on the total monomer units.

4. 4. The fluorine-containing copolymer according to claim 1, which has a melt flow rate at 372° C. of 30.0 to 39.9 g / 10 min.

5. 5. The fluorine-containing copolymer according to any one of claims 1 to 4, which has a melt flow rate at 372°C of 33.0 to 39.9 g / 10 min.

6. An injection molded article comprising the fluorine-containing copolymer according to any one of claims 1 to 5.

7. A coated electric wire having a coating layer containing the fluorine-containing copolymer according to any one of claims 1 to 5.

8. 6. A molded article comprising the fluorine-containing copolymer according to any one of claims 1 to 5, which is a container, a tube, a film or a wire coating.

Citation Information

Patent Citations

  • Herbicidal 2,6-substituted pyridine

    JP1994040813A

  • Extrusion method for fluoropolymers

    JP1999512217A

  • Improvement of perfluoropolymer

    JP2009540105A

  • Tetrafluoroethylene / hexafluoropropylene copolymer and method for producing the same, and electric wire

    JP2011514407A

  • Composition, and method for producing foam molded material and electric wire

    JP2014224228A